Proteocephalus macrophallus (Cestoda: Proteocephalidae) Infecting Cichla kelberi (Cichliformes: Cichlidae) as a Bioindicator for Trace Metal Accumulation in a Neotropical River from Southeastern Brazil - Leite, Lucas Aparecido Rosa [UNESP]; dos Reis Pedreira Filho, Walter; de Azevedo, Rodney Kozlowiski; Abdallah, Vanessa Doro (Springer Nature, 2021)
Here, we evaluate the potential for trace metal accumulation of nine elements (Al, Cr, Mn, Fe, Ni, Cu, As, Cd, and Pb) in the cestodes Proteocephalus macrophallus parasitizing the tucunaré, Cichla kelberi, in the Jacaré-Guaçú River, southeastern Brazil. For metal quantification in the tissues of hosts and parasites, an inductively coupled plasma–mass spectrometer (ICP-MS) was used. All recovered trace metals were in higher amounts in cestodes than in the tissues (muscle, intestine, and liver) of their hosts. The best accumulated element was lead, with concentrations up to 10,000 times higher in parasites than in the liver of the fish hosts. Other well-accumulated elements were cadmium, with concentrations up to 238 times higher in parasites, and aluminum and nickel, with concentrations ranging from 140 to 128 times higher in parasites. In addition, non-infected fish had higher concentrations of cadmium and lead in their tissues than infected fish. In infected fish, the size of the cestodes’ infrapopulations influenced in the concentrations of arsenic, cadmium, and lead in the hosts tissues. In general, specimens of P. macrophallus had a good capacity for metal accumulation for all the analyzed elements, with emphasis on Al, Ni, Cd, and Pb, and therefore could be a useful tool in trace metal bioaccumulation indication.
Keywords: Accumulation indicators; Environmental parasitology; Fish parasitology; Heavy metal pollution; Trace metal accumulation